DAYA BUNUH BAHAN NABATI SERBUK BIJI PAPAYA TERHADAP KEMATIAN LARVA Aedes aegypti ISOLAT LABORATORIUM B2P2VRP SALATIGA - Margo Utomo; Siti Amaliah; Febria Ari Suryati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2010)
Background: Dengue Haemorrhagic Fever (DHF) is a disease caused by Dengue virus and infected by Aedes aegypti mosquito that is indicated by acute fever for about 2-7 days followed by the nuisance on capillary blood artery and blood freezing system so that, it caused bleeding and even death. Some factors that influence the spreding increase of DHF case are very complex they are population growth, no effective mosquito control in endemic. Any expedient to fight against the diseases by controlling the vector has been done, both chemically and naturally. Objective: To analyze the the priciest doze to reach up the most effective impact papaya seed powder towards amounth death Aedes aegypti larvae. Method: A randomized post test only control group design, on 660 tails, per bowl 20 tails of Aedes aegypti larvae instar III in B2P2VRP Salatiga, divided into the treatment and control group. Controlled variable were temperature and pH of water media. Length of contact with papaya seed powder were 24 hours. Analyzing data with one way Anova test. Result: The most effective doze at 200 mg/100 ml, reach up to 100 % of death in 24 hours. With Anova test p-value = 0,000 (p < 0,05), there is significant difference of larvae death on several dozes, only at 20 mg/100 ml and 40 mg/100 ml dozes there are no significant difference of larvae death (p-value = 0,763 p > 0,05). Conclusion: There is significant difference lethal effect on several dozes of papaya seed powder with the Aedes aegypti larvae death, and the most effective doze is 200mg/100 ml.Keyword: Papaya seed powder, several dozes, Aedes aegyti larvae.